A Rare Case: Stenosis Doudeni Congenital et Causa Ladd Band Eet Causa Malrotation with Situs Inversus in 12 Days Old Baby - Thaihutu, Yhohan Ziantprayogi; Rifa’i, Muhammad Syahibuddin (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
We are sharing a rare presentation of congenital duodenal obstruction with combined intrinsic and extrinsic causes with situs inversus, namely, duodenal stenosis with gastrointestinal malrotation in a neonate. The patient underwent successful exploratory laparotomy, Ladd's procedure, and appendicectomy were carried out. Early recognition of signs and symptoms, prompt corrective surgery, and adequate optimization of metabolic components post-operatively are important to determine the decreased morbidity and mortality of neonates.